2023
DOI: 10.3390/molecules28093656
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic, Headspace and Sensory Profile, and Antioxidant Capacity of Fruit Juice Enriched with Salvia officinalis L. and Thymus serpyllum L. Extract: A Potential for a Novel Herbal-Based Functional Beverages

Abstract: Since certain constituents are not naturally present in pure fruit juices, incorporating herbal extracts can provide specific sensory properties to the beverages and improve their biopotential. In our previous research, it was found that sage (Salvia officinalis L.), wild thyme (Thymus serpyllum L.), and combinations of their extracts had the highest total phenolic content and a unique composition of volatile compounds, which can contribute to the aromatic and antioxidant qualities of functional products. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 128 publications
0
3
0
2
Order By: Relevance
“…These results are in agreement with our previous study, which showed that fortified fruit juices have higher antioxidant activity by oxygen radical absorbance capacity (ORAC) assay. [19] This is most likely due to the different structures of the phenolic components, which are present in higher concentrations in the plant extracts than in the pure fruit juices. Our findings are also consistent with the results of a previous study by Ogundele et al, [14] who indicated that the ability of fruit juice formulations to scavenge free radicals increased with increasing plant extract amounts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with our previous study, which showed that fortified fruit juices have higher antioxidant activity by oxygen radical absorbance capacity (ORAC) assay. [19] This is most likely due to the different structures of the phenolic components, which are present in higher concentrations in the plant extracts than in the pure fruit juices. Our findings are also consistent with the results of a previous study by Ogundele et al, [14] who indicated that the ability of fruit juice formulations to scavenge free radicals increased with increasing plant extract amounts.…”
Section: Resultsmentioning
confidence: 99%
“…[40] Plant extracts can be used not only to enhance antioxidant activity, but also to improve the sensory properties of functional beverages and to develop new formulations acceptable to consumers. [19]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca içerdikleri fenolik bileşenler, antioksidanlar gibi biyoaktif bileşenler ile yüksek lif, vitamin ve minerallerin sağlığı olumlu yönde etkilemesi sebebiyle de popülerliklerini korumaktadırlar (Ghinea et al, 2022). Meyve suları biyoaktif bileşenler bakımından zengin olmalarına rağmen, elde edildikleri meyvelerin ham maddeleri ile karşılaştırıldığında, uygulanan işlemler sonucunda önemli oranda kayıplar olduğu belirtilmektedir (Törrönen et al, 2012;Maleš et al, 2023). Bu aşamada çeşitli aromatik bitki ekstraktlarının meyve sularının biyoaktif bileşen kompozisyonunu zenginleştirmek amacıyla kullanımı bir alternatif olarak karşımıza çıkmaktadır (Gomez et al, 2023;Maleš et al, 2023).…”
Section: Introductionunclassified
“…Meyve suyu üretiminde portakal ve ananas ile birlikte en çok üretimi yapılan elma suyunda da diğer meyve sularında uygulanan ısıl işlemler sonucu biyoaktif bileşenlerde kayıplar görülmektedir. Literatür çalışmalarında kekik, adaçayı, biberiye gibi aromatik bitkilerden elde edilen bitkisel ekstraktların içerdikleri hidroksisinnamik asitler, flavonlar ve terpenler gibi biyoaktif bileşenlerin elma sularında fenolik içerikleri, antioksidan özellikleri ve duyusal nitelikleri olumlu yönde etkilediği belirtilmiştir (Carović-StanKo et al, 2016;Raudone et al, 2017;Abd Rashed & Rathi, 2021;Maleš et al, 2023).…”
Section: Introductionunclassified